Integrated application of macrophytes and zooplankton for wastewater treatment - Prakash, Diwakar; Kumar, Ram; Rajan, Kumar; Patel, Abhishek; Yadav, Devesh Kumar; Dhanker, Raunak; Khudsar, Faiyaz A. (Frontiers in Environmental Science, 2022)
The increasing amount of sewage has become a serious concern globally, demanding sustainable solutions. The constructed wetland system (CWS) can be installed at the wastewater discharge site and properly screened bio-purifiers can be used for efficient wastewater treatment. Filter-feeding zooplankton have the potential to graze on bacteria and reduce biological oxygen demand. However, higher suspended particles choke the zooplankton filtering appendages. An integrated application of zooplankton and macrophytes can solve the problems by reducing contaminants and providing the surface area for zooplankton to take refuge. Using three different approaches: (a) screening of natural bio-purifiers through time series study, (b) assessment of sewage treatment potential of screened bio-purifiers in the CWS and, (c) evaluation of the growth potential of screened bio-purifiers in untreated wastewater, this study explored the combined use of macrophyte and zooplankton in the CWS. The 3-year time series study in the vicinity of the wastewater discharge area recorded the zooplankton, Brachionus angularis and Moina macrocopa as highly indicative zooplankton. The top two highly indicative macrophytes are Typha and Phragmites. Under laboratory conditions, the population growth rates of B. angularis and M. macrocopa were significantly higher in wastewater without any external nutrient source than those in control with algae as a food source. The integrated application of zooplankton (B. angularis and M. macrocopa) macrophytes (Typha and Phragmites) in CWS yielded upto 56% reduction in the total bacterial count and upto 92% reduction in BOD along with substantial increase in the DO level. The present results strongly suggested the use of CWS planted with macrophytes and inoculated by zooplankton. The usefulness of this system is further supported by the natural occurrence of selected species, as it is easy to maintain, has low installation cost, and excellent efficiency in treating wastewater. As both the zooplankton species are preferred live feed for rearing of fish larvae, the present results suggested the use of zooplankton and macrophytes for treatment of wastewater, reduction of sludge, and harvest of live feeds for the aquaculture industry to augment circularity and promote decentralized wastewater treatment.